2023
DOI: 10.3389/fmicb.2023.1225944
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of chloropicrin fumigation on soil microbe recovery and growth promotion of Panax notoginseng

Abstract: IntroductionPanax notoginseng is a precious Chinese medicinal material. Soil fumigation can control soil-borne disease and overcome the continuous cropping obstacles of P. notoginseng. However, chloropicrin (CP) fumigation can kill non-target soil microorganisms and reduce microbial diversity, but the long-time impacts of CP fumigation on soil microbial are less reported.MethodsWe studied the long-term effects of CP fumigation on soil microbes with high-throughput gene sequencing, and correlated the changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Soil fumigation with ammonium bicarbonate and lime can directly influence pathogens, improve the soil environment by decreasing soil acidity, and reshape soil microbial community structure, thereby directly or indirectly preventing and controlling soilborne diseases ( Liu et al, 2016 ; Deng et al, 2021 ). It has been reported that soil fumigation altered soil microflora in plant monoculture systems by changing soil microbial community structure and stimulating the potentially beneficial microbial consortia ( Li et al, 2016 ; Wang et al, 2023 , 2024 ). The structure of microbial communities separates clearly under fumigated (N, NB, and LNB) and non-fumigated (GZ) treatments as revealed by PCoA based on Weighted Unifrac and Unweighted Unifrac analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Soil fumigation with ammonium bicarbonate and lime can directly influence pathogens, improve the soil environment by decreasing soil acidity, and reshape soil microbial community structure, thereby directly or indirectly preventing and controlling soilborne diseases ( Liu et al, 2016 ; Deng et al, 2021 ). It has been reported that soil fumigation altered soil microflora in plant monoculture systems by changing soil microbial community structure and stimulating the potentially beneficial microbial consortia ( Li et al, 2016 ; Wang et al, 2023 , 2024 ). The structure of microbial communities separates clearly under fumigated (N, NB, and LNB) and non-fumigated (GZ) treatments as revealed by PCoA based on Weighted Unifrac and Unweighted Unifrac analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Soil fumigation can control and kill root-knot nematodes, soil-borne pathogens, and weeds [43]. Wang et al [44] reported that the inhibition rate of Phytophthora spp. was still 97.8% and 75.0% in the second and third years after chloropicrin fumigation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The cropping obstacle, characterized by reduced crop yield and quality resulting from prolonged monoculture continuous cropping, has been observed in both annual and perennial crops (Tan et al 2021 ). After harvest, replanting of traditional Chinese medicine will also cause soil continuous cropping obstacles, resulting in slow growth, increased incidence of soil-borne diseases, and decreased yields (Tagele et al 2023 ; Wang et al 2023b ). The continuous cropping obstacle of traditional Chinese medicine has always been a bottleneck problem in the development of traditional Chinese medicine, especially in the cultivation of American ginseng ( Panax quinquefolius L.) (Xiao et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%